GENDER EXPECTATIONS AND THEIR CROSSINGS IN PLAYTIME ACTIVITIES IN EARLY CHILDHOOD EDUCATION - Jéssica Fernanda Schmitz Coelho; Priscila Renata Martins; André Luiz dos Santos Silva; Denise Bolzan Berlese (Journal of Physical Education)
ABSTRACT The present study aimed to analyze gender crossings in the pedagogical practices and playtime activities in a nursery group - "Maternal 3”, highlighting what was expected from boys and girls in regard to their behavior. As a data collection strategy, semi-structured interviews and observation, in which notes were taken and registered in a journal, were the methods adopted. This process took six months. It was evident that gender produced normative pedagogical practices which tried to make invisible the subjects who deviated from the center. This invisibility seemed necessary to reinforce the power relations that were present in the routines and crossed the pedagogical practices, keeping the students in “their places".